1994
DOI: 10.1093/jat/18.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Urinary Benzodiazepines Using Solid-Phase Extraction and Gas Chromatography-Mass Spectrometry

Abstract: A solid-phase extraction and GC-MS confirmation method was developed for certain urinary diazolo- and triazolobenzodiazepines, including the metabolites of lorazepam, clonazepam, alprazolam, and triazolam. The latter two do not form benzophenones, and the others are not readily confirmed by conventional thin-layer chromatography or GC-MS techniques. Samples were hydrolyzed with glucuronidase at 37 degrees C, adjusted to pH 4.5, extracted with Bond Elut Certify columns, dried, and derivatized using BSTFA with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…Instrumental methods of analysis have employed gas chromatography [7], with prior derivatization [8], high performance liquid chromatography [9] with mass spectrometry www.elsevier.com/locate/forsciint Forensic Science International 166 (2007) 209-217 [10]. Gas chromatography/mass spectrometry using chemical derivatives such as BSTFA [11] and HFBA [12] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumental methods of analysis have employed gas chromatography [7], with prior derivatization [8], high performance liquid chromatography [9] with mass spectrometry www.elsevier.com/locate/forsciint Forensic Science International 166 (2007) 209-217 [10]. Gas chromatography/mass spectrometry using chemical derivatives such as BSTFA [11] and HFBA [12] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, capillary GC coupled to mass spectrometry (MS) is the method of choice for most of the toxicological analysis. Electronic impact GC-MS provides a selective analytical procedure for the analysis of BZP in biological samples [14][15][16][17] although several authors have demonstrated that the negative-ion chemical ionisation (NCI) is a more sensitive technique [18][19][20][21]. However, this method is generally tedious to apply because BZP are very polar and thermally unstable, so they cannot be evaporated and chromatographed without decomposition, unless previous derivatisation [22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Liquid-liquid extraction can be tedious and time consuming, where as SPE extraction methods described in previous investigations though were efficient and reliable, but were not rapid enough for emergency toxicological screening and required the preparation of various buffers and solutions. Many investigators have directed their systematic toxicological analysis to the use of gas chromatography (GC), [5][6][7][8] thin-layer chromatography (TLC), [9][10][11] and high-performance liquid chromatography (HPLC) 12,13 as drug screening tools. GC coupled with mass detector can identify low concentrated compounds if only derivatization step is performed for certainly highly polar and thermolabile drugs and metabolites.…”
Section: Introductionmentioning
confidence: 99%